2022
DOI: 10.31729/jnma.7532
|View full text |Cite
|
Sign up to set email alerts
|

Primary Caesarean Section among Multiparous Pregnant Women Visiting a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Caesarean section is one of the most common obstetric operations performed. Primary caesarean section in multiparous women means the first caesarean section done in the multiparity who had previously delivered vaginally. This study aimed to find out the prevalence of primary caesarean section among multiparous pregnant women visiting a tertiary care centre. Methods: A descriptive cross-sectional study was conducted among multiparous women in a tertiary care centre from 15 June 2020 to 14 June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Multiparity also showed a marginal trend of correlation with caesarean section, at a non-significant level though. In this aspect, a recent descriptive cross-sectional study was conducted among multiparous women in a tertiary care center and showed that the prevalence of primary caesarean section in multiparous women was found to be higher than the other studies performed in similar settings [ 38 ]. Another study conducted on 8732 deliveries showed that caesarean section rates in the primiparous women were higher in all age groups when compared with multiparous women [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiparity also showed a marginal trend of correlation with caesarean section, at a non-significant level though. In this aspect, a recent descriptive cross-sectional study was conducted among multiparous women in a tertiary care center and showed that the prevalence of primary caesarean section in multiparous women was found to be higher than the other studies performed in similar settings [ 38 ]. Another study conducted on 8732 deliveries showed that caesarean section rates in the primiparous women were higher in all age groups when compared with multiparous women [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is true that there is no universally established maximum number of C-sections a woman can have before the risks of serious complications increase significantly. The uterus’ ability to heal and withstand the stress of multiple C-sections varies from person to person, and individual and medical factors play a role [ 6 ].…”
Section: Introductionmentioning
confidence: 99%